Antiobesity Potential of Butterfly Pea Flower (Clitoria Ternatea): A Literature Review - Nur Aini Djunet; Muflihah Rizkawati (Universitas Wijaya Kusuma Surabaya, 2023)
Obesity is a health problem with an increasing prevalence every year in many countries including Indonesia. Obese patients are at risk for complications related to some non-communicable diseases. The difficulty of losing weight in obese patients is due to low awareness of a good lifestyle, appropriate dietary patterns, and discipline in taking drugs to prevent complications. However, the need for drug consumption takes a long time. The risk of side effects arising from long-term drug use needs to be considered. Using herbal plants as an additional dietary intervention could be a better choice. This review described the benefits of the butterfly pea (Clitoria ternatea) flower as antiobesity. This study is a literature review by searching preceding published articles in Pubmed, ScienceDirect, Cochrane, and Google Scholar journals. The keywords used are (Clitoria ternatea) OR (Bunga Telang) OR (Butterfly pea) AND (Obesity) OR (Antiobesity). Articles are limited by publication period from 2012 to 2022 and then selected based on the criteria. This literature review concluded that the administration of Clitoria ternatea extracts (CTE) can become an alternative antiobesity by inhibiting weight gain, increasing adipose lipolysis, and decreasing the expression of adipogenic and lipogenic proteins.